2013
DOI: 10.1089/brain.2012.0123
|View full text |Cite
|
Sign up to set email alerts
|

Altered Connectivity of the Balance Processing Network After Tongue Stimulation in Balance-Impaired Individuals

Abstract: Some individuals with balance impairment have hypersensitivity of the motion-sensitive visual cortices (hMT + ) compared to healthy controls. Previous work showed that electrical tongue stimulation can reduce the exaggerated postural sway induced by optic flow in this subject population and decrease the hypersensitive response of hMT + . Additionally, a region within the brainstem (BS), likely containing the vestibular and trigeminal nuclei, showed increased optic flow-induced activity after tongue stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…This is an ongoing challenge with non-invasive neuromodulation studies in general: reproduction of a comparable procedural experience for sham-arm subjects as compared with active-arm subjects. Wildenberg at al. (2013) hypothesized that the afferent output from tongue stimulation enters the brainstem in proximity to the vestibular and trigeminal nuclei, moving upwards to the cortex, and is able to influence cortical processing of visual motion.…”
Section: Cfc -Cross Frequency Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an ongoing challenge with non-invasive neuromodulation studies in general: reproduction of a comparable procedural experience for sham-arm subjects as compared with active-arm subjects. Wildenberg at al. (2013) hypothesized that the afferent output from tongue stimulation enters the brainstem in proximity to the vestibular and trigeminal nuclei, moving upwards to the cortex, and is able to influence cortical processing of visual motion.…”
Section: Cfc -Cross Frequency Correlationmentioning
confidence: 99%
“…A crucial observation is that this approach to sensory neuromodulation enables stimulation of brainstem regions. But the modulatory effects progress up from the brainstem to areas including the visual cortex and parieto-insular vestibular cortex (Wildenberg, 2013). And, importantly, the modulation signal follows endogenous sensory pathways.…”
Section: Cfc -Cross Frequency Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…This non-intuitive discovery underlies the clinical focus of the tongue stimulator for balance disorders. Wildenberg et al (2013) hypothesized that the afferent output from tongue stimulation enters the brainstem in proximity to the vestibular and trigeminal nuclei, moving upwards to the cortex, and is able to influence cortical processing of visual motion. Leonard et al (2017) undertook an imaging study with multiple sclerosis subjects to assess the effects of PONS stimulation over a 14-weeks treatment period.…”
Section: Somatosensory Stimulationmentioning
confidence: 99%
“…Wildenberg et al (2010) showed that stimulation that doesn't convey information about body posture or gravity can improve balance performance in people with balance dysfunction [102]. They've also investigated the effects of electrotactile tongue stimulation on balance performance and have used imaging techniques such as MRI and fMRI to show that stimulation upregulates visual sensitivity to optic flow in people with balance impairments [102][103][104][105].…”
Section: Mechanismmentioning
confidence: 99%